Presence of anti-Leishmania antibodies in candidates for kidney transplantation - Franca, Adriana de Oliveira; Rodrigues da Cunha, Giovana Masselli; Oliveira, Leticia Pereira; Carvalho, Lidia Raquel de [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Cavalheiros Dorval, Maria Elizabeth (Elsevier B.V., 2020)
Objectives: Visceral leishmaniasis (VL) is a progressive disease that, left untreated, is typically fatal. The purpose of this investigation was to detect Leishmania sp. infection in hemodialysis patients who had received multiple blood transfusions at a private clinic in Campo Grande, Mato Grosso do Sul state, Midwest Brazil. Methods: Fifty randomly selected volunteers were interviewed for collection of demographic, socioeconomic, and epidemiological data. Indirect immunofluorescence (titers positive when >= 1:40) and rK39 immunochromatographic tests were employed for serological investigation. Results: Males predominated (60%). Age ranged from 20 to 77 years. Most subjects reported being on hemodialysis for at least one year (94%) and 84% were candidates for kidney transplantation, 67% of whom were on the waiting list. Leishmania sp. infection was detected in 32%. Contact with infected dogs was the only variable associated with infection. Conclusions: Under immunocompromised conditions, VL is opportunistic and potentially fatal. Despite existing risks, screening for VL is not performed in asymptomatic donors and recipients. The detection of anti-Leishmania antibodies in these patients reinforces the need for infection screening before immunosuppressive treatment is initiated to reduce not only the risks of VL development and severity, but also mortality rates in cases of reactivation of latent infection. (C) 2020 The Authors. Published by Elsevier Ltd on behalf of International Society for Infectious Diseases.
Keywords: Visceral leishmaniasis; Infection; Donors; Recipients; Immunocompromised patients; Hemodialysis